Monitoreo del anti-inflamatorio piroxicam y delanti-hipertensivo atenolol en un arroyo urbano entrês Lagoas, Brasil (2015)
Pharmaceuticals production and their consumption by the world population have increased in recent years; as a result, these contaminants have reached the water.